Fabrication of bio-engineered chitosan nanoformulations to inhibition of bacterial infection and to improve therapeutic potential of intestinal microflora, intestinal morphology, and immune response in infection induced rat model - Xiao Wan; Liu Liu; Lu Ding; Zhiqiang Zhu (Taylor & Francis Group, 2022)
Overdosage of antibiotics used to prevent bacterial infections in the human and animal gastrointestinal tract would result in disturbing of intestinal barrier, significant misbalancing effects of intestinal microflora and persuading bacterial resistance. The main objective of the present investigation is to design and develop novel combinations of organic curcumin (Cur) and antimicrobial peptide (Amp) loaded chitosan nanoformulations (Cur/Amp@CS NPs) to improve significant effects on antibacterial action, immune response, intestine morphology, and intentional microflora. The antibacterial efficiency of the prepared nanoformulations was evaluated using Escherichia coli (E. coli) induced bacterial infections in GUT of Rat models. Further, we studied the cytocompatibility, inflammatory responses, α-diversity, intestinal morphology, and immune responses of treated nanoformulations in rat GUT models. The results indicated that Cur/Amp@CS NPs are greatly beneficial for intestinal microflora and could be a prodigious alternative of antibiotics.